Rhipicephalus appendiculatus (Acari: Ixodidae): dynamics of Thogoto virus infection in female ticks during feeding on guinea pigs. - Kaufman, W; Nuttall, P (2003)
Engorged nymphs (Rhipicephalus appendiculatus) were inoculated parenterally with Thogoto (THO) virus (approximately 1 microl per nymph; 10(6)-10(7) PFU/ml). The adult females which resulted were used as the source of infected ticks for this study. Hemolymph, salivary glands, synganglion, gut, ovary, and Malpighian tubules were collected on each day of the blood meal and titrated for THO virus by plaque assay. The percent of tissues infected with virus was 16% or less on the day of attachment. Percent infection rose for all tissues throughout 6-7 days of feeding, reaching 40-100% infection during the rapid phase of engorgement. For the first 4 days of feeding, virus titer in the synganglion was higher than in salivary glands (means of 6.4-34.7 PFU/synganglion and 1.6-8.8 PFU/salivary gland pair). From days 5-7, virus titer was generally higher in the salivary gland than the synganglion (means of 422, 408, and 817 PFU/gland pair and means of 62, 811, and 9 PFU/synganglion). However, because a salivary gland pair is much heavier than a synganglion, the virus concentration in the synganglion was much higher than in the salivary gland during the slow phase of feeding. During the rapid phase of feeding, the difference in virus titer between the synganglion and salivary gland reduced. This difference between the early and late stages of feeding may explain why a previous study [J. Gen. Virol. 70 (1989) 1093], using immunofluorescence and immuno-gold labelling, failed to detect virus in the salivary gland early in feeding. These data provide evidence to explain that R. appendiculatus can transmit THO virus within 24h of attachment, an important epidemiological finding.